Primigravida's Readiness in Dealing with Childbirth Considering the Mother's Social Characteristics - Erma Nur Fauziandari (Journal Of Nursing Practice, 2021)
Background: Indonesian Population Demographic Survey (IDHS) in 2017 stated that the Maternal Mortality Rate (MMR) in Indonesia was 309/100,000 live births. According to Ristica (2017) the high maternal mortality rate in Indonesia is caused by the unpreparedness of the mother in facing childbirth. Maternal unpreparedness is usually seen among primigravida who struggle in preparing for childbirth as they have yet experience in delivering. Geniofam in Muthoharoh explained (2018) the factors that influence mother's readiness including knowledge, education, socio-culture and economy.Purpose: This study aimed to determine the mother social characteristic (age, education, occupation) that affect the readiness of primigravida in facing childbirthMethods: This type of research is analytical research with an observational approach. The sample in this study involved 53 primigravida on the third trimester of pregnancy. Data collection was carried out by filling out questionnaires on the readiness of mothers to face childbirth by respondents.Results: The results of statistical tests showed that age, education, or occupation did not affect mother's readiness in dealing with childbirth with p value > 0.05.Conclussions:  mother’s social characteristics do not affect the readiness of primigravida in facing childbirth.